2009
DOI: 10.1016/j.scitotenv.2009.04.039
|View full text |Cite
|
Sign up to set email alerts
|

Comparative chronic toxicity of homo- and heterocyclic aromatic compounds to benthic and terrestrial invertebrates: Generalizations and exceptions

Abstract: Comparative chronic toxicity of homo-and heterocyclic aromatic compounds to benthic and terrestrial invertebrates: Generalizations and exceptions Leon Paumen, M.; de Voogt, W.P.; van Gestel, C.A.M.; Kraak, M.H.S. General rightsIt is not permitted to download or to forward/distribute the text or part of it without the consent of the author(s) and/or copyright holder(s), other than for strictly personal, individual use, unless the work is under an open content license (like Creative Commons). Disclaimer/Complai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 43 publications
0
13
0
Order By: Relevance
“…Nevertheless, they found an exception in an enchytraeid species (E. crypticus), where the median lethal concentration was higher than expected [12]. Critical body residues (Table 1) in E. albidus estimated using the BAF of 19.5 kg soil/kg fresh weight organism (Table 2) are in agreement with the critical body residue levels reported in the literature for chemicals with a narcotic mode of action (typically 2-8 mmol/kg [31,32]) suggesting that PHE is acting as a narcotic chemical also in enchytraeids.…”
Section: Phe Effects On Enchytraeids Survival and Reproductionmentioning
confidence: 84%
See 2 more Smart Citations
“…Nevertheless, they found an exception in an enchytraeid species (E. crypticus), where the median lethal concentration was higher than expected [12]. Critical body residues (Table 1) in E. albidus estimated using the BAF of 19.5 kg soil/kg fresh weight organism (Table 2) are in agreement with the critical body residue levels reported in the literature for chemicals with a narcotic mode of action (typically 2-8 mmol/kg [31,32]) suggesting that PHE is acting as a narcotic chemical also in enchytraeids.…”
Section: Phe Effects On Enchytraeids Survival and Reproductionmentioning
confidence: 84%
“…Paumen and co-authors [12] showed that narcosis was the main mode of action for most of the PAHs, including PHE [23]. Nevertheless, they found an exception in an enchytraeid species (E. crypticus), where the median lethal concentration was higher than expected [12].…”
Section: Phe Effects On Enchytraeids Survival and Reproductionmentioning
confidence: 94%
See 1 more Smart Citation
“…Naphthalene, anthracene, pyrene, benz[a]anthracene, and benzo[a]pyrene were selected as test compounds to cover a wide range of physicochemical properties (Table 1). Anthracene was used instead of phenanthrene due to its low a max (Table 1), since results from several studies have shown that only PAHs exceeding a certain a max can exert acute toxicity [11,[18][19][20]. Phenanthrene and anthracene are isomers with very similar partitioning and diffusion properties, and the bioconcentration is therefore expected to be rather similar for these two PAHs.…”
Section: Springtail Experimentsmentioning
confidence: 99%
“…Nevertheless, the effects of ON on the surface ocean are unclear due to the large uncertainty in the sources and magnitudes of deposition. Even less is known about the potential human and ecosystem toxicity of ON (Paumen et al, 2009).…”
Section: Atmospheric Relevancementioning
confidence: 99%